The effect of estroprogestagen therapy on lipid status in menopause depending on the drug administration route - Čitlučanin, Goran; Ivović, Miomira; Tančić-Gajić, Milina; Canović, Fadil; Stojanović, Miloš; Marina, Ljiljana; Arizanović, Zorana; Djogo, Aleksandar; Vujović, Svetlana; Gerginić, Vladimir (Vojnosanitetski pregled, 2021)
Background/Aim. In menopausal women lipid and lipoprotein values are important predictors of development of cardiovascular diseases (CVD). The use of estrogens reduces levels of low density lipoprotein cholesterol (LDL-C) and lipoprotein A [Lp(a)], and increases levels of triglycerides (TG) and high density lipoprotein cholesterol (HDL-C) depending on the dose and route of administration. Simultaneous administration of progesterone, depending on the type, can have different effects on lipids. The aim of the study was to examine the effect of estroprogestagen therapy on the lipid metabolism of women in menopause, depending on the administration route. Methods. A study was conducted as prospective clinical interventional study with controlled parallel groups. It included 64 women in menopause, divided into three groups: the group 1 (n = 22) on oral therapy with estroprogestagens, the group 2 (n = 17) on transdermal patch therapy with estroprogestagens and the group 3 (n = 25) treated with estroprogestagens given intramuscularly. The following biochemical parameters in the serum were determined: total cholesterol (TC), HDL-C, LDL-C, TG, Lp(a), apoprotein A (Apo-A), apoprotein B (Apo-B), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol, progesterone, testosterone, sex hormone-binding globulin (SHBG), dehydroepiandrosterone sulfate (DHEA-SO4), prolactin and thyroid-stimulating hormone (TSH), prior to administration of the menopausal hormonal therapy (MHT), as well as after sixth months and 2–5 years from the beginning of the therapy. The statistical significance of the difference in values obtained was examined independently and depending on the route of MHT application. Results. MHT, regardless of the administration route, led to a statistically significant continuous decrease of TC, LDL-C and Apo-B levels and the continuous increase of HDL-C and Apo-A levels. Serum levels of TC, LDL-C, HDL-C, Lp(a), Apo-A and Apo-B did not show a statistically significant differences among groups of women given MHT by different routes. It was found that the serum level of Apo-A increased significantly with the rise of estradiol, and the values of LDL and Apo-B decreased regardless of the route of the MHT application. Conclusion. MHT introduced in time, regardless of the route of administration, has beneficial effects on the lipid status of menopausal women and consequently might prevent numerous cardiovascular diseases that are the leading cause of mortality.